Gas venting that bypasses the feather edge of marine hydrate, offshore Mauritania. (December 2017) - Li, Ang; Davies, Richard J.; Mathias, Simon A.; Yang, Jinxiu; Hobbs, Richard; Wilson, Miles
Abstract: Methane can be released from the vast marine hydrate reservoirs that surround continents into oceans and perhaps the atmosphere. But how these pathways work within the global carbon cycle now and during a warmer world is only partially understood. Here we use 3-D seismic data to identify what we interpret to be a gas venting system that bypasses the hydrate stability zone (HSZ) offshore of Mauritania. This venting is manifested by the presence of the acoustic wipe-out (AWO) across a densely faulted succession above a salt diapir and a set of morphological features including a substantial, ∼260 m wide and ∼32 m deep, pockmark at the seabed. The base of the HSZ is marked by a bottom simulating reflector (BSR) which deflects upwards above the diapir, rather than mimicking the seabed. We use a numerical modelling to show that this deflection is caused by the underlying salt diapir. It creates a trapping geometry for gas sealed by hydrate-clogged sediment. After entering the HSZ, some methane accumulated as hydrate in the levees of a buried canyon. Venting in this locality probably reduces the flux of gas to the landward limit of feather edge of hydrate, reducing the volume of gas that would be susceptible for release during a warmer world. Highlights: A gas venting system is imaged using 3-D seismic data offshore Mauritania. Free gas bypassed the HSZ and migrated along the faults to reach the seabed. The local BSR shoaling is caused by more heat conduction of a salt diapir. Massive warming-induced methane seafloor release is unlikely since the year 2000.